Pemanfaatan Flutter Pada Pengembangan Aplikasi Mobile M-Cyber Untuk Manajemen Keuangan - Pusvita, Ester Ayuk; Sinaga, Wahyu Adi Saputra (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Technological advancements in the digital era have transformed personal financial management, yet many individuals still struggle to track their income and expenses regularly. For instance, students at PTKIN in East Java often face financial leakage due to consumptive lifestyles and lack of control. While mobile applications could offer an effective solution in this digital age, most people still rely on conventional spreadsheets, as depicted in the film Home Sweet Loan. Therefore, this study aims to develop M-Cyber, a Flutter-based application designed to help users record transactions, monitor finances, and plan savings. Leveraging Flutter, the app can operate efficiently across multiple platforms (Android/iOS), supported by Visual Studio Code (VS Code) and the Dart programming language, which ensures consistent and functional interface development. Using a qualitative case-study approach, this research is expected to provide a solution for uncontrolled financial management while promoting users' financial stability.